The application of vagus nerve stimulation and deep brain stimulation in depression - Mohr, Pavel; Rodriguez, Mabel; Slavíčková, Anna; Hanka, Jan (Neuropsychobiology, 2011)
Despite the progress in the pharmacotherapy of depression, there is a substantial proportion of treatment-resistant patients. Recently, reversible invasive stimulation methods, i.e. vagus nerve stimulation (VNS) and deep brain stimulation (DBS), have been introduced into the management of treatment-resistant depression (TRD). VNS has already received regulatory approval for TRD. This paper reviews the available clinical evidence and neurobiology of VNS and DBS in TRD. The principle of VNS is a stimulation of the left cervical vagus nerve with a programmable neurostimulator. VNS was examined in 4 clinical trials with 355 patients. VNS demonstrated steadily increasing improvement with full benefit after 6-12 months, sustained up to 2 years. Patients who responded best had a low-to-moderate antidepressant resistance. However, the primary results of the only controlled trial were negative. DBS involves stereotactical implantation of electrodes powered by a pulse generator into the specific brain regions. For depression, the targeted areas are the subthalamic nucleus, internal globus pallidus, ventral internal capsule/ventral striatum, the subgenual cingulated region, and the nucleus accumbens. Antidepressant effects of DBS were examined in case series with a total number of 50 TRD patients. Stimulation of different brain regions resulted in a reduction of depressive symptoms. The clinical data on the use of VNS and DBS in TRD are encouraging. The major contribution of the methods is a novel approach that allows for precise targeting of the specific brain areas, nuclei and circuits implicated in the etiopathogenesis of neuropsychiatric disorders. For clinical practice, it is necessary to identify patients who may best benefit from VNS or DBS.
Keywords: Vagus Nerve Stimulation; klinické zkoušky jako téma; Deep Brain Stimulation; Depressive Disorder, Treatment-Resistant; vagová stimulace; deprese nereagující na léčbu; lidé; nervus vagus; Clinical Trials as Topic; Vagus Nerve; Antidepressive Agents; antidepresiva; Brain; hluboká mozková stimulace; mozek; Humans